Six new species of Hylotribus Jekel, 1860 from Brazil (Coleoptera, Anthribidae, Anthribinae, Discotenini) - de Quei, Fernando Luiz Cunha Avila Villar; Mermudes, José Ricardo M. (Zootaxa, 2014)
Hylotribus Jekel, 1860 is a distinct genus of South American Anthribidae characterized by a fragmented antebasal pronotal carina, and includes nine species, eight of which are endemic to Chile, and one species from Peru. We here describe and illustrate six new species from the Atlantic Rainforest biome in Brazil based on unidentified material deposited in various collections: Hylotribus fluminensis Queiroz & Mermudes sp. nov. (Rio de Janeiro, Rio de Janeiro State); Hylotribus sublimis Queiroz & Mermudes sp. nov. (Campos do Jordão, São Paulo State); Hylotribus plaumanni Queiroz & Mermudes sp. nov. (Seara, Santa Catarina State); Hylotribus frontispeltastes Queiroz & Mermudes sp. nov. (São José do Barreiro, Serra da Bocaina, São Paulo State and Serra do Caraça, Minas Gerais State); Hylotribus gauchus Queiroz & Mermudes sp. nov. (Cambará do Sul, Rio Grande do Sul State); and Hylotribus involucer Queiroz & Mermudes sp. nov. (São José do Barreiro, Serra da Bocaina, São Paulo State). A key is provided to the species of Hylotribus in Brazil.